Help desk management system - Siew Pei, Low (2005)
Help Desk Management System is basically a central point where problems or issues are reported and consequently managed and coordinated in other words, Help Desk Management System is a system for customers support center to find out and deal with the problems logged from the customers through phone calls or self service portal.An effective Help Desk can fulfill customers'needs in providing them the proper solution to solve their problems in a short period of time. The Help Desk Management System that I developed for my project is the Performance Analysis Module of Ardent Helpluz. For the time being,Ardent Helpluz is lack of Performance Analysis Module.Employer is not able to generate any analysis to find out the performance of his company. Therefore, employer could not identify the cause of loss and profit in order to improve the productivity of the company. Hence,Performance Analysis Module plays an important role in a Help Desk Management System. With the development of Performance Analysis Module in Ardent Helpluz,Ardent Helpluz can be enhanced to a more reliable Help Desk Management System.